2010
DOI: 10.1210/jc.2010-0606
|View full text |Cite
|
Sign up to set email alerts
|

A 16-Week Randomized Clinical Trial of 2000 International Units Daily Vitamin D3Supplementation in Black Youth: 25-Hydroxyvitamin D, Adiposity, and Arterial Stiffness

Abstract: Daily 2000 IU vitamin D supplementation may be effective in optimizing vitamin D status and counteracting the progression of aortic stiffness in black youth. Plasma 25(OH)D concentrations in response to the 2000 IU/d supplementation are negatively modulated by adiposity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
234
6
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(256 citation statements)
references
References 40 publications
12
234
6
2
Order By: Relevance
“…A recent study on 24 black adolescents reported a significant decrease of aortic PWV during a 16-week vitamin D supplementation. 25 The crucial question is whether subjects with relatively mild hypovitaminosis, such as in our series, may have any benefit from vitamin D supplementation in terms of cardiovascular risk. A meta-analysis of 18 randomized controlled trials with vitamin D supplementation for osteoporosis in general population showed a significant 7% decrease in all-cause mortality, which is probably a higher benefit than can be expected from simple reduction of osteoporotic fractures.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A recent study on 24 black adolescents reported a significant decrease of aortic PWV during a 16-week vitamin D supplementation. 25 The crucial question is whether subjects with relatively mild hypovitaminosis, such as in our series, may have any benefit from vitamin D supplementation in terms of cardiovascular risk. A meta-analysis of 18 randomized controlled trials with vitamin D supplementation for osteoporosis in general population showed a significant 7% decrease in all-cause mortality, which is probably a higher benefit than can be expected from simple reduction of osteoporotic fractures.…”
Section: Discussionmentioning
confidence: 86%
“…12 Venous blood samples were drawn in fasting state, and frozen serum samples stored at -80 degrees were used for biochemical laboratory analyses in the series. 25 …”
Section: Examinations and Materialsmentioning
confidence: 99%
“…On average, supplementation with high-doses of vitamin D (2000 IU) in healthy children has resulted in increments of serum 25OHD concentrations ranging from 37 to 52 nmol/L [146,167].…”
Section: Sample Sizementioning
confidence: 99%
“…[34,145,146]. It is important to note that the relationship between vitamin D intake and serum 25OHD concentrations is highly dependent on height and weight of individuals [146].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation